An analysis of Javanese language test characteristic using the Rasch model in R program - Muchlisin Muchlisin; Djemari Mardapi; Farida Agus Setiawati (Program Pascasarjana Universitas Negeri Yogyakarta & HEPI, 2019)
One skill required to solve a problem in the 21st century is communication. Two international languages that are important in communication and thought at school are English and German language. However, beside international language, the local language, such as the Javanese language, is also essential and need to be maintained. The purpose of this study is to analyze the Javanese language test characteristics. This study was explorative research with secondary data collected by documentation of 220 students responses to the 50 multiple choice item of Javanese language test in the 11th grade of vocational high school. Data were analyzed using the Rasch model assisted by R program. Rasch model fits the data with 42 items after three times calibration. Based on difficulty level, ICC, and items reliability, there were 28 of 42 items (66.67%) that were good. This study finds out that generally, the Javanese language test is in the moderate category of difficulty. Hence, the need of evaluating the Javanese language test to make a better test that gives more accurate information about examinees' ability is crucial. The evaluation of the Javanese language test can be used to plan the next learning to get better Javanese language learning.